Offline-Based Tutoring in Cijeruk Village, Dayeuhluhur District, Cilacap Regency - Nurhayati, Ai; Lugiana, Yuda; Robiatul A, Wahda; Nazila, Siti Desi; Noor F, Neng Dewi; Septiani, Lisma; Fauziah, Irma Silvia; Assidqi, Hasbi; Maulana, Deni; Sopia, Dea; Wahyuni, Arni Sri; Hendrawan, Budi (AbdimasMu UMTAS, 2024)
Offline-based tutoring activities in Cijeruk Village, Dayeuhluhur District, Cilacap Regency were carried out for the UMTAS KKN-T service program targeting elementary school students living in Cijeruk Village. This activity aims to (1) assist students in understanding material that is not yet understood, (2) help with assignments given to students so that students do not experience difficulties, (3) in addition to participating in reducing corona virus clusters in the education sector, Offline-based tutoring also results in Elementary School (SD) students better understanding the material provided and being more helpful in doing schoolwork.